2020
DOI: 10.1177/0141778919895498
|View full text |Cite
|
Sign up to set email alerts
|

From Feminist Anarchy to Decolonisation: Understanding Abortion Health Activism Before and After the Repeal of the 8thAmendment

Abstract: This article analyses abortion health activism (AHA) in the Irish context. AHA is a form of activism focused on enabling abortion access where it is restricted. Historically, AHA has involved facilitating the movement of abortion seekers along ‘abortion trails’ (Rossiter, 2009). Organisations operate transnationally, enabling access to abortion care across borders. Such AHA is a form of feminist anarchism, resisting prohibitions on abortion through direct action. However, AHA work has changed over tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…For example, while the Irish government reported that twenty-five legal abortions occurred inside Ireland in the year 2016, the UK Department of Health reported that that 3,265 women living in Ireland obtained abortions in English clinics in that same year (Cullen, 2017; IFPA, 2017). From the 1980s through to the present day, diasporic and transnational pro-choice activist groups have provided information, funding and infrastructural and emotional support for abortion travel to England (Duffy, 2020, this issue). Furthermore, from 2008 onwards, access to illegal abortion pills inside Ireland has also become a significant form of exit from Ireland’s abortion ban (Sheldon, 2016).…”
Section: Irelandmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, while the Irish government reported that twenty-five legal abortions occurred inside Ireland in the year 2016, the UK Department of Health reported that that 3,265 women living in Ireland obtained abortions in English clinics in that same year (Cullen, 2017; IFPA, 2017). From the 1980s through to the present day, diasporic and transnational pro-choice activist groups have provided information, funding and infrastructural and emotional support for abortion travel to England (Duffy, 2020, this issue). Furthermore, from 2008 onwards, access to illegal abortion pills inside Ireland has also become a significant form of exit from Ireland’s abortion ban (Sheldon, 2016).…”
Section: Irelandmentioning
confidence: 99%
“…Domestic abortion access outside of the law has emerged through ‘underground’ clinics (in Poland) and the circulation of medication abortion pills (in Poland and Ireland) (Mishtal, 2015; Sheldon, 2016). Abortion travel abroad has been actively facilitated by transnational networks of pro-choice activists who assist women to travel to other jurisdictions (see Ciaputa, 2019; Duffy, 2020, this issue). The sheer volume of non-compliance by abortion-seekers in these countries demonstrates the extent of the continued demand for abortion and the availability of abortion outside of state-prescribed legal pathways.…”
Section: Feminist Activism In the Context Of Morality Policy And Church–state Relationsmentioning
confidence: 99%
“…The campaign too largely ignored the difficulties of access to abortion for people of colour, migrants with precarious legal status in Ireland, trans people, young people, people in abusive and controlling relationships (MERJ, 2019). These are the same people who continue to feel the sharpest edges of the restrictions of Irish law, too often left behind by the new legislation, still relying on travel, self-managed abortion and the mutual aid of feminist activism to escape from undesired pregnancy (MERJ, 2019; de Londras, 2020, this issue; Duffy, 2020, this issue; Side, 2020, this issue). Migrant and trans reproductive rights activists in particular continue to make (righteous) demands for atonement from the official campaign, and much work remains to be done (de Londras, forthcoming).…”
Section: The Referendum and The New Lawmentioning
confidence: 99%
“…Transnational abortion health activism has been a continuous solidarity practice between women in Ireland and abroad—especially in England, where groups like the Liverpool Ireland Abortion Support Service (1979–1985), Escort (1988–2003) and the Abortion Support Network (2009–present) have been and are still active. Deidre Duffy (2020, this issue) traces the past and present of these organisations through the lenses of feminist anarchy and decolonisation to understand their systems of support for abortion seekers as political acts of resistance to oppressive governing structures. The forms of solidarity work that abortion health activists engage in often involve caring practices like advice, support, hosting and other activities that have been traditionally depoliticised by their association with domestic, feminised spaces.…”
Section: Transnational Activismmentioning
confidence: 99%
“…They constituted a kind of ‘network of escape’, making movement possible, reducing risks and holding onto a ‘vital wager’, as Verónica Gago (2018, p. 339) puts it, when considering the significance of migration routes from Bolivia to Argentina. Open Line Counselling and the Women’s Information Network provided underground assistance in Ireland, and IWASG, ESCORT and LASS provided assistance in Britain (Fletcher, 2017; Duffy, 2020, this issue). While Liverpool-based LASS and ESCORT did not bear particular traces of diaspora organising, IWASG shared a diasporic consciousness with its Spanish equivalent at the time (Rossiter, 2009; see also IWASG, 1988).…”
Section: Messy Genealogies: Citing Imelda’s Sourcesmentioning
confidence: 99%